Hospitalizaciones por neumonía adquirida en la comunidad - Abreu Suárez, Gladys; Pérez Brunet, Aurelia; Fuentes Fernández, Gladys; Portuondo Leyva, Reina; Pérez Orta, Miosotis (Revista Cubana de Pediatría, 2017)
No lleva resumen.Es una comunicación breve